2020
DOI: 10.1186/s12913-020-05310-6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond coverage: a qualitative study exploring the perceived impact of Gabon’s health insurance plan on access to and quality of prenatal care

Abstract: Background Access to affordable and adequate healthcare in a health system determines the universal health coverage achievement for all residents in a country. Achieving access to healthcare requires the availability of a financing system that ensures access to and provision of adequate care, regardless of the ability to pay. In sub-Saharan Africa, accessibility, use and coverage of prenatal visits are very low and poor, which reduces the quality of care. This paper explored the impact of a soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In both Ghana and Gabon, for example, there have also been accounts of medicine stock-outs and financial challenges hindering the implementation of their health insurance schemes. [35][36][37] This evidence reinforces the notion that implementing effective social health protection schemes requires taking into account quality healthcare that responds to the population's needs in the design of these schemes.…”
Section: Discussionsupporting
confidence: 66%
“…In both Ghana and Gabon, for example, there have also been accounts of medicine stock-outs and financial challenges hindering the implementation of their health insurance schemes. [35][36][37] This evidence reinforces the notion that implementing effective social health protection schemes requires taking into account quality healthcare that responds to the population's needs in the design of these schemes.…”
Section: Discussionsupporting
confidence: 66%
“…Jiang et al ( 38 ) suggested that the “health status” of the insured is also a key factor in the perceptions of benefits. Moreover, Sadak et al and Sanogo et al ( 39 , 40 ) have shown that the experience of the insured is fundamental to evaluating the perceptions of medical insurance benefits.…”
Section: Methodsmentioning
confidence: 99%
“…The enablers identified related to the providers of care attitudes towards the implementation of the EML included satisfaction with the coverage of the social health insurance scheme 61 , positive attitude towards the provision of ICT support to improve their medical knowledge and skills 71 , and satisfaction with the quality of medicines 72 .…”
Section: Attitudes Regarding Programme Acceptability Appropriateness ...mentioning
confidence: 99%
“…The main barriers to motivation to change included underpayment of healthcare workers [60][61][62] , high workload as a result of shortage of staff 63,64 and limited supervision, career and training opportunities 62,65 . Other motivation related barriers cited include low levels of motivation to work due to lack of essential medicines and equipment for use in facilities 36 , delay in the payment of claimant rebates to health staff 61 , and limited scientific evidence-informed decision-making 66 .…”
Section: Motivation To Changementioning
confidence: 99%